2021
DOI: 10.3989/gya.0334201
|View full text |Cite
|
Sign up to set email alerts
|

Improving the oxidative stability of breadsticks with ginkgo (Ginkgo biloba) and ginseng (Panax ginseng) dried extracts

Abstract: Recently, there has been a growing interest in the use of natural antioxidants instead of synthetic ones. The aim of this work was to determine the effect of ginkgo and ginseng dried extracts as natural antioxidants on the stability of lipids in breadsticks over 55 days of storage at room temperature compared to butylated hydroxytoluene. Ginkgo and ginseng dried extracts were incorporated individually into breadstick formulae at levels of 0.5 and 1% to enhance its oxidative stability in storage. The increases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In studies conducted on Treccine prepared with sunflower oil and fortified with vegetable matrices, it was determined that Ginkgo and Ginseng significantly reduced the PV increase during 60-day storage up to a maximum of 9 meq O 2 /kg oil in relation to the percentage of extract included in the recipe (the higher the extract content, the lower the PV increase), whereas in the control sample (without vegetable extract), the PV increased up to 15 meq O 2 /kg oil in 25-day storage [62]. Caponio et al [63] studied the peroxide value evolution in a traditional bakery product called Taralli prepared in Apulia (Italy) with different oils (extra virgin olive oil, olive oil, olive pomace oil and refined palm oil) and detected an increase in PV in all different recipes even though EVOO showed the lowest significant increase.…”
Section: Free Acidity and Peroxide Value Of The Extracted Oilsmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies conducted on Treccine prepared with sunflower oil and fortified with vegetable matrices, it was determined that Ginkgo and Ginseng significantly reduced the PV increase during 60-day storage up to a maximum of 9 meq O 2 /kg oil in relation to the percentage of extract included in the recipe (the higher the extract content, the lower the PV increase), whereas in the control sample (without vegetable extract), the PV increased up to 15 meq O 2 /kg oil in 25-day storage [62]. Caponio et al [63] studied the peroxide value evolution in a traditional bakery product called Taralli prepared in Apulia (Italy) with different oils (extra virgin olive oil, olive oil, olive pomace oil and refined palm oil) and detected an increase in PV in all different recipes even though EVOO showed the lowest significant increase.…”
Section: Free Acidity and Peroxide Value Of The Extracted Oilsmentioning
confidence: 99%
“…Hammad et al [62] studied breadsticks fortified with Grinko and Ginseng and reported an inverse correlation between oxidative indices (peroxide value, p-anisidine value, totox) and sensory parameters such as odour, taste and texture. This agrees with our results.…”
Section: Sensory Analysismentioning
confidence: 99%